2020
DOI: 10.1101/2020.07.05.188433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional succinate dehydrogenase deficiency and loss of ascorbic acid transporter SLC23A1 are pathognomonic adverse features of clear cell renal cancer

Abstract: ABSTRACTBackgroundReduced succinate dehydrogenase (SDH) activity resulting in adverse succinate accumulation was previously thought to be relevant only in 0.05-0.5% of kidney cancers associated with germline SDH mutations (categorized ‘SDH-deficient Renal Cell Carcinoma’ in the 2016 WHO classification)ResultsWe show that under-expression of SDH subunits r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…L2HG competitively inhibits the Ten-Eleven-Translocation (TET) enzymes, including TET2, which has been shown to have an important role in cancer immunity 15,45 . ccRCC is also characterized by loss of succinate dehydrogenase resulting in the accumulation of oncogenic succinate, which also inhibits the TET enzymes, further contributing to the widespread genomic aberrant hypermethylation in the malignancy 46,47 .…”
Section: (Iv) Tumor-associated Metabolitesmentioning
confidence: 99%
“…L2HG competitively inhibits the Ten-Eleven-Translocation (TET) enzymes, including TET2, which has been shown to have an important role in cancer immunity 15,45 . ccRCC is also characterized by loss of succinate dehydrogenase resulting in the accumulation of oncogenic succinate, which also inhibits the TET enzymes, further contributing to the widespread genomic aberrant hypermethylation in the malignancy 46,47 .…”
Section: (Iv) Tumor-associated Metabolitesmentioning
confidence: 99%
“…They confirmed that succinate increased HIF-1α protein and mRNA expression with an intensity dependent on the incubation time. An important effect of succinate accumulation is the hypermethylation of histones and DNA cytosine [ 67 , 83 ] as a result of the succinate-mediated inhibition of histone lysine demethylases (KDMs) and TETs [ 74 , 84 ]. Succinate-mediate hypermethylation changes the expression profile of genes, leading to the activation of epithelial-to-mesenchymal transition.…”
Section: Succinatementioning
confidence: 99%
“…As mentioned before, mitochondrial oncometabolites cause epigenetic changes in cancer cells, boosting oncogenesis and cancer progression. SDH deficient tumors are characterized by hypermethylation of histones and DNA cytosine [14,43], as a result of the succinate-mediated inhibition of histone lysine demethylases (KDMs) and TETs [26,44]. The hypermethylation changes the expression profile of specific genes, leading for instance to the activation of the EMT program, as demonstrated in pheochromocytomas and paragangliomas knocked-down for SDHB [45].…”
Section: Mitochondrial Oncometabolites and Cancer Biologymentioning
confidence: 99%